Extracellular CIRP augments inflammation in acute kidney injury via NKG2D-positive macrophages - Zhang, Fangming; Jin, Hui; Tan, Chuyi; Wang, Ping; Brenner, Max (Frontiers in Immunology, 2026)
IntroductionThe mechanism by which extracellular cold-inducible RNA-binding protein (eCIRP) aggravates renal ischemia/reperfusion (RIR) injury leading to acute kidney injury (AKI) is poorly understood. The natural killer group 2D (NKG2D) receptor and its ligand MULT-1 are key immunoregulatory mechanisms promoting responses to damaged and inflamed cells.MethodsWe subjected wild-type and CIRP−/− mice to RIR. We then used immunohistochemistry (IHC), flow cytometry, and Western blotting to assess NKG2D and MULT-1 in kidney tissues, macrophages, and renal tubular epithelial cells (RTECs), and ELISA to assess TNFa and IL-6. ResultsThe expression levels of NKG2D and its ligand MULT-1 were significantly elevated in wild-type mice subjected to RIR compared with sham. In contrast, CIRP−/− mice exhibited markedly reduced expression of both NKG2D and MULT-1 after RIR compared to wild-type mice. In vitro, eCIRP stimulated the expression of NKG2D in peritoneal macrophages and of MULT-1 in RTECs. Treatment of eCIRP-stimulated peritoneal macrophage and RTEC co-cultures with an NKG2D-neutralizing antibody significantly and markedly downregulated supernatant levels of TNFa and IL-6.DiscussionIn conclusion, eCIRP induces NKG2D+ macrophages and MULT-1+ RTECs, and their interaction further increases the inflammatory response. Targeting the NKG2D/MULT-1 may reduce RIR-induced inflammation and thus attenuate AKI.